1995
DOI: 10.1111/j.1365-2125.1995.tb04499.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tenidap sodium on the pharmacodynamics and plasma protein binding of warfarin in healthy volunteers.

Abstract: The mean percentage of unbound warfarin in the tenidap group (0.08% ± 0.09) was significantly different (P = 0.047) from that in the placebo group (-0.03% 0.10) but this was not considered to be clinically meaningful. 6 These data indicate that prothrombin times should be monitored during concomitant administration of tenidap and warfarin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…This increase was similar at both the pre- [11] showed that tenidap does not displace tolbutamide from plasma protein binding sites. On the other hand, tenidap has been found to displace warfarin, although the extent to which this occurred was not considered to be clinically meaningful [13].…”
Section: Discussionmentioning
confidence: 99%
“…This increase was similar at both the pre- [11] showed that tenidap does not displace tolbutamide from plasma protein binding sites. On the other hand, tenidap has been found to displace warfarin, although the extent to which this occurred was not considered to be clinically meaningful [13].…”
Section: Discussionmentioning
confidence: 99%
“…It can also cause gastrointestinal ulceration, hemorrhage, and inhibition of platelet aggregation 19,69,70 . Of the other non-steroidal anti-inflammatory drugs, flurbiprofen 71 83 .…”
Section: Drugs Affecting Haemostasismentioning
confidence: 99%
“…It should also be noted that for many of these drugs no enhancement of warfarin activity has been demonstrated. The non-steroidal anti-inflammatory drugs with an apparently minimal effect on warfarin activity include etodolac 80 , ibuprofen 81 , naproxen 82 and tenidap 83 .…”
Section: Drugs Affecting Haemostasismentioning
confidence: 99%
See 2 more Smart Citations